Building codes illustrated a guide to understanding the 2021 international building code - Ching, Francis D. K. 1943-; Winkel, Steven R (Hoboken Wiley, 2022)
"This unique reference to the 2021 International Building Code marries the graphic skills of bestselling author Frank Ching with the code expertise of Steven Winkel, FAIA. It pulls out portions of the building code that are most relevant for the architect and provides an easy-to-understand interpretation in both words and illustrations. This Seventh Edition will include three new chapters: Plumbing Fixture Counts, Elevators, and Special Construction, and an extensively expanded chapter on Existing Buildings"
Includes bibliographical references and index.
Keywords: Buildings -- Specifications; Standards, Engineering